Influencing Sustainable Mobility with Social Influence - Neef, Robin (Student Undergraduate Research E-journal!, 2015)
This paper explores how a socio-psychological approach strengthened with social influence theory can contribute to attaining sustainable mobility by evaluating four mobility projects in the Netherlands as a response to the lack of that approach in Dutch planning practice. Findings indicate that social influence can contribute effectively to current mobility approaches. Social influence is activated when either social proof is triggered through descriptive social norms or when commitment is triggered through competitions with financial incentives.